2009
DOI: 10.1111/j.1365-2486.2008.01708.x
|View full text |Cite
|
Sign up to set email alerts
|

Forest–flood relation still tenuous – comment on ‘Global evidence that deforestation amplifies flood risk and severity in the developing world’ by C. J. A. Bradshaw, N.S. Sodi, K. S.‐H. Peh and B.W. Brook

Abstract: In a recent paper in this journal, Bradshaw and colleagues analyse country statistics on flood characteristics, land cover and land cover change, and conclude that deforestation amplifies flood risk and severity in the developing world. The study addresses an important and long-standing question, but we identify important flaws. Principal among these are difficulties in interpreting country statistics and the correlation between population and floods. We review current knowledge, which suggests that the remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 23 publications
4
87
0
1
Order By: Relevance
“…Although previous work on the relationship between land-cover change and Q using lumped meso-and macro-scale catchment data has experienced some difficulty demonstrating unequivocal results (e.g. Van Dijk et al, 2012), possibly stronger conclusions may be obtained by selecting catchments within similar regions (in this case central Puerto Rico; cf. Peña-Arancibia et al, 2010).…”
Section: H E Beck Et Almentioning
confidence: 99%
See 3 more Smart Citations
“…Although previous work on the relationship between land-cover change and Q using lumped meso-and macro-scale catchment data has experienced some difficulty demonstrating unequivocal results (e.g. Van Dijk et al, 2012), possibly stronger conclusions may be obtained by selecting catchments within similar regions (in this case central Puerto Rico; cf. Peña-Arancibia et al, 2010).…”
Section: H E Beck Et Almentioning
confidence: 99%
“…Van Dijk et al, 2012), or in time, due to land-cover changes altering the climate (Van der Molen, 2002;Pielke et al, 2007). Several mesoscale atmospheric modelling studies have produced conflicting results regarding the existence of such a relationship for Puerto Rico (Van der Molen et al, 2006;Comarazamy and González, 2011).…”
Section: Potential Explanations For the Lack Of Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…As forests can reduce flooding by acting as sponges (trapping water during heavy rainfall, and releasing it slowly into streams), which decreases the severity of floods and maintains stream flows during dry periods, several nations have invested in forest protection or reforestation [32][33][34] (Figure 1). However, some authors suggested that removal of trees does not affect large flood events [35]. Thus, the need for large-scale forest protection and more reforestation to help reduce the frequency and severity of floods to protect human wellbeing was pointed out [32].…”
Section: Reforestation For Ecosystem Servicesmentioning
confidence: 99%